Встреча: для среднего школьного возраста / Дэн Поблоки - Поблоки Дэн (Дом теней, 2021)
Экземпляры: ф.20 (2021) / Инвентарный номер: 57422 / Цена: / Сис.шифр: 84(7Сое) / Авт.знак: П 41 / ББК: 83.84(7Сое)6-445